2016
DOI: 10.1080/02770903.2016.1198375
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver perception of asthma management of children in the context of poverty

Abstract: Objective Low-income caregivers of young children with high-risk asthma experience social stressors and illness-related demands that may impede effective home asthma management. Knowledge of the caregiving experience in the context of poverty is limited. Methods Convenience sampling methods were used to recruit low-income caregivers of children aged 7–12 years, who are frequently in the Emergency Room (ED) for uncontrolled asthma. Thirteen caregivers participated in focus groups that were designed to elicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…Caregiver emotional and financial strains to implement a total home smoking ban may elucidate the complexity in reducing a child's SHS exposure . Caregiver misunderstanding of the ubiquitous penetration of SHS in their home and/or residing in multiunit dwellings may have contributed to the null effect of the intervention . Alternatively, health behavior of parents who smoke may explain the lack of decreasing SHS exposure in this sample of high‐risk children.…”
Section: Discussionmentioning
confidence: 97%
“…Caregiver emotional and financial strains to implement a total home smoking ban may elucidate the complexity in reducing a child's SHS exposure . Caregiver misunderstanding of the ubiquitous penetration of SHS in their home and/or residing in multiunit dwellings may have contributed to the null effect of the intervention . Alternatively, health behavior of parents who smoke may explain the lack of decreasing SHS exposure in this sample of high‐risk children.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, they do not know what to do, feel desperate, constantly making an effort in order to prevent their children from getting sick, sleep beside their children at night and constantly keep their eyes on their children, and always take leave from their jobs during disease periods, which affects their professional life. 20,21 Challenges were feelings of guilt and blame, concerns about reproduction, feeling helpless and alone, feeling worried about the future, the burden and problems during the diagnostic process. The interpersonal challenges that were identified were the feeling of isolation, negative impacts on relationships, financial impacts, lack of knowledge and understanding among their community, lack of support, and lack of help from the health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in previous studies, the measures most frequently taken by families in order to cope with the disease were determined to be as follows: keeping the room moist and ventilated, not smoking at home, frequently changing bed sheets, using hypoallergenic beds, and limiting physical activity. 20,21,25 In studies of the experiences of families, the families having child with asthma, emphasized the lack of training and psychological support provided by healthcare professionals. 19,[33][34][35] Moreover, in previous studies, it was reported that families had problems with school personnel concerning managing asthma and that many families did not send their children to school during periods of exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of asthma in pediatrics requires caregiver competencies such as the identification and avoidance of triggers, implementation of environmental control protocols at home, recognition of symptoms, and administration of medications (7). Caregivers experience the challenges of identifying and managing allergies, being hypervigilant, differentiating asthma symptoms from other health concerns, and knowing when to seek emergency care (8). These could make asthma caregiving stressful.…”
Section: Introductionmentioning
confidence: 99%